The effect of metformin on ameliorating neurological function deficits and tissue damage in rats following spinal cord injury: A systematic review and network meta-analysis - Zhou, Long-yun; Chen, Xu-qing; Yu, Bin-bin; Pan, Meng-xiao; Fang, Lu; Li, Jian; Cui, Xue-jun; Yao, Min; Lu, Xiao (Frontiers in Neuroscience, 2022)
Spinal cord injury (SCI) is a devastating condition with few treatment options. Metformin, a classical antidiabetic and antioxidant, has extended its application to experimental SCI treatment. Here, we performed a systematic review to evaluate the neurobiological roles of metformin for treating SCI in rats, and to assess the potential for clinical translation. PubMed, Embase, China National Knowledge Infrastructure, WanFang data, SinoMed and Vip Journal Integration Platform databases were searched from their inception dates to October 2021. Two reviewers independently selected controlled studies evaluating the neurobiological roles of metformin in rats following SCI, extracted data, and assessed the quality of methodology and evidence. Pairwise meta-analyses, subgroup analyses and network analysis were performed to assess the roles of metformin in neurological function and tissue damage in SCI rats. Twelve articles were included in this systematic review. Most of them were of moderate-to-high methodological quality, while the quality of evidence from those studies was not high. Generally, Basso, Beattie, and Bresnahan scores were increased in rats treated with metformin compared with controls, and the weighted mean differences (WMDs) between metformin and control groups exhibited a gradual upward trend from the 3rd (nine studies, n = 164, WMD = 0.42, 95% CI = -0.01 to 0.85, P = 0.06) to the 28th day after treatment (nine studies, n = 136, WMD = 3.48, 95% CI = 2.04 to 4.92, P < 0.00001). Metformin intervention was associated with improved inclined plane scores, tissue preservation ratio and number of anterior horn motor neurons. Subgroup analyses indicated an association between neuroprotection and metformin dose. Network meta-analysis showed that 50 mg/kg metformin exhibited greater protection than 10 and 100 mg/kg metformin. The action mechanisms behind metformin were associated with activating adenosine monophosphate-activated protein kinase signaling, regulating mitochondrial function and relieving endoplasmic reticulum stress. Collectively, this review indicates that metformin has a protective effect on SCI with satisfactory safety and we demonstrate a rational mechanism of action; therefore, metformin is a promising candidate for future clinical trials. However, given the limitations of animal experimental methodological and evidence quality, the findings of this pre-clinical review should be interpreted with caution.